IMPLEMENTATION OF “METHODOLOGICAL MASTERY DAY” AND “METHODOLOGICAL MASTERY HOUR” IN PRESCHOOL EDUCATIONAL INSTITUTIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article highlights the issues of introducing the “Methodical Mastery Day” and “Methodical Mastery Hour” in preschool education institutions based on the Presidential Decree of the Republic of Uzbekistan No. PF-152 dated September 30, 2024. These activities serve to ensure the continuous professional development of teachers, enhance their knowledge and skills, and improve the efficiency of the educational process. The study analyzes the content of these activities, their organizational mechanisms, the role of trainers and master trainers, the significance of the “Virtual Professional Development” platform, as well as opportunities for applying international best practices and innovative technologies.